Textanalyse oder Textinterpretation? Überlegungen aus textlinguistischer Sicht - Błachut, Edyta (Studia Germanica Posnaniensia, 2019)
Dealing with texts may mean using various research methods. The present paper discusses two such methodological approaches: text analysis and text interpretation. It is concerned, initially theoretically, with the question how these approaches can be explained from the text-linguistics point of view and separated from each other. After that a short text material is used to illustrate the thesis that analyzing and interpreting texts are two different forms of dealing with texts.